What do verbal fluency tasks measure? Predictors of verbal fluency performance in older adults - Shao, Zeshu; Janse, Esther; Visser, Karina; Meyer, Antje S. (Frontiers in Psychology, 2014)
This study examined the contributions of verbal ability and executive control to verbal fluency performance in older adults (n = 82). Verbal fluency was assessed in letter and category fluency tasks, and performance on these tasks was related to indicators of vocabulary size, lexical access speed, updating, and inhibition ability. In regression analyses the number of words produced in both fluency tasks was predicted by updating ability, and the speed of the first response was predicted by vocabulary size and, for category fluency only, lexical access speed. These results highlight the hybrid character of both fluency tasks, which may limit their usefulness for research and clinical purposes.